MANAJEMEN KURIKULUM PENDIDIKAN ANAK USIA DINI DALAM MENINGKATKAN KEPUASAN PELANGGAN STUDI KASUS: TAMAN KANAK-KANAK HAMZANWADI PANCOR 2019/2020 - m.rudi gunawan parozak; Fadma Rosita (JUPE : Jurnal Pendidikan Mandala, 2019)
The purpose of this research is to know how the management of early childhood curriculum in Hamzanwadi Kindergarten observed from aspects of: curriculum planning, curriculum organization, school and class level curriculum implementation, and curriculum evaluation. Know the inhibiting factors and supporting factors of the application of the  curriculum. Knowing about the level of customer satisfaction as well as the results achieved by the graduates of the applied curriculum.This research uses descriptive qualitative research type, with research subjects are teacher, principal, expert staff, and parents of students  Kindergarten Hamzanwadi academic year 20182019. method of data collection using observation method, interview, and documentation. The validity of data is done by using data triangulation. Data analysis techniques used in this study is data collection, data reduction, data presentation, and withdrawal and testing conclusions.The results showed that: 1) curriculum planning is done by academic creative. The academic creative team consists of teachers representing each level in each branch. The curriculum is designed based on the development of the curriculum set by the government that is the curriculum 2013. 2) organizing the curriculum is done by the government. 3) the implementation of the curriculum is done well. Teachers are very categorical in carrying out the curriculum. Teachers work together to implement school-level and class-level curricula. Implementation is on schedule and according to the curriculum. 4) curriculum evaluation has been done well. From the evaluation evaluation, there is still a need for revise or perfection of the curriculum because it is still in the 2013 curriculum trial stage. Curriculum replacement for now is not necessary. 5) the inhibiting factor in the curriculum implementation is the difficulty in presenting the media from the natural materials during learning. Characteristics of developing children make teachers difficult in conditioning the class and deliver the material. Factors supporting the implementation of the curriculum in the availability of sufficient funds, facilities and complete infrastructure, and good human resources capabilities. 6) the level of customer satisfaction in the academic year 2017/2018 has been achieved with the implementation of curriculum management at the Hamzanwadi Kindergarten.